The evolution of physical attributes in elite ski racers aged 17 to 20 during the Olympic training period - Golovachev, A. I.; Kolykhmatov, V. I.; Grushin, A. A.; Shirokova, S. V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to investigation of the development of physical attributes in elite ski racers aged 17 to 20 during the Olympic training period.